Appropriate waist circumference cut off level for hypertension screening among admission students at Chiang Mai University - Thaikruea, Lakkana; Yavichai, Siriboon; Nuntakwang, Chadchadaporn; Yoonut, Kulyapa (Biomedical Sciences and Clinical Medicine, 2023)
Background There is no official cut off value of waist circumference (WC) measured at the superior iliac crest level (WCI) for health screening young adolescents in Thailand. This study aimed to determine a correlation between WCI and measurements at the midpoint between the lower costal margin and superior iliac crest (WCM), and define appropriate WCI and body mass index (BMI) cut off levels for health screening admission students in northern Thailand. Methods Students passing the entrance exams for the academic year, 2012, had health screening, which included physical examination, and WC, BMI, and blood pressure (BP) measurements. Results Of 2,525 students receiving both WCI and WCM measurements, 59.50% were female. Correlation between the WCI and WCM measurements was 0.86, with 5.10% of the students having high BP. The WCM of 90 cm in males and 80 cm in females (WCM9080) was set as the standard for receiver operating characteristics (ROC) analysis of high blood pressure. The WCI of 90 cm in males and 80 cm in females (WCI9080) had significantly larger areas (0.6837) than those of WCM9080 (0.6278). WCI9080 had 44.53% sensitivity, 92.99% specificity, and 90.53% corrected classification. Conclusions The proposed WCI cut off value was WCI9080. A further cohort study is needed to confirm these values. For national reference, this study recommends measuring at the umbilical level, due to its feasibility. Also, an appropriate cut off level should be determined in the context of the Thai population.